The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1016/bs.irn.2018.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Human Pharmacological Conditioning of the Immune and Endocrine System: Challenges and Opportunities

Abstract: In this chapter, we review recent studies on conditioned pharmacological effects on immune and endocrine responses in humans, and discuss challenges and opportunities for bringing these effects into clinical practice. By altering physiological mechanisms in part independent of pharmacological agents, pharmacological conditioning has high clinical relevance, as illustrated in some patient studies. Methodological challenges for further investigation include broadening the spectrum of opportunities for conditione… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…Explorations of this are necessary to find what internal biological processes can be conditioned besides the ones already found. For example, the immune and endocrine systems can be conditioned, and the type of paired environmental cue had a significant effect on the strength of the conditioning [139][140][141][142].…”
Section: Drug Conditioning: Proto-cognitive Aspects Of Physiological ...mentioning
confidence: 99%
“…Explorations of this are necessary to find what internal biological processes can be conditioned besides the ones already found. For example, the immune and endocrine systems can be conditioned, and the type of paired environmental cue had a significant effect on the strength of the conditioning [139][140][141][142].…”
Section: Drug Conditioning: Proto-cognitive Aspects Of Physiological ...mentioning
confidence: 99%
“…To optimally integrate conditioning principles in drug regimens, it would therefore be important to explain the potential of pharmacological conditioning by primarily focusing on the therapeutic effects of MTX (40). Moreover, previous trials that made use of pharmacological conditioning showed a clinically meaningful reduction of side effects (35,41,42). Nevertheless, it is of utmost importance to closely monitor side effects during the whole duration of treatment.…”
Section: Testing the Hypothesismentioning
confidence: 99%
“…First, an association is formed during the acquisition phase, in which two stimuli are repeatedly presented at the same time. In the second phase, the strength of the learned association is subsequently tested during the evocation phase (see Figure 3 for an overview of a conditioning paradigm) [23,45]. In the acquisition phase, an initial neutral stimulus, like a gustatory or olfactory stimulus (conditioned stimulus, CS), is paired with an unconditioned stimulus (UCS), for example an immunomodulating drug.…”
Section: The Learned Immune Responsementioning
confidence: 99%
“…In conditioning paradigms, it has shown that after this association has been formed, re-exposure of the CS alone, without the presence of the immunomodulating drug in the evocation phase, can now demonstrate a conditioned response (CR; Figure 3). This conditioned immune response is present on a behavioral level, for example by a conditioned taste aversion, and on an immunological level by mimicking the initial drug effect [23,45]…”
Section: The Learned Immune Responsementioning
confidence: 99%